2005
DOI: 10.1111/j.1365-2745.2005.01040.x
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary advantages of mast seeding in Fagus crenata

Abstract: Summary1 Two non-mutually exclusive hypotheses have been proposed to explain the evolutionary advantages of mast seeding (the intermittent production of large crops of flowers or seeds by a population of perennial plants). Mast seeding could have evolved as a result of increased pollination efficiency in mast-flowering years and/or as an anti-predator adaptation that increases the survival of seeds by alternately starving seed predators in non-mast years and satiating them in mast years. 2 We investigated annu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
85
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(90 citation statements)
references
References 43 publications
3
85
0
2
Order By: Relevance
“…Based on scant circumstantial evidence from the distribution of trees, Finckh & Paulsch (1995) and Veblen (1982) speculated that Austral parakeets might disperse the seeds, but seed-carrying has not been observed. A few studies (Kon et al 2005) have shown that seed predators exert selective pressure on tree reproductive synchrony, but no previous work has been directed at the interaction of pre-dispersal predation with pehuén masting cycles.…”
Section: Introductionmentioning
confidence: 99%
“…Based on scant circumstantial evidence from the distribution of trees, Finckh & Paulsch (1995) and Veblen (1982) speculated that Austral parakeets might disperse the seeds, but seed-carrying has not been observed. A few studies (Kon et al 2005) have shown that seed predators exert selective pressure on tree reproductive synchrony, but no previous work has been directed at the interaction of pre-dispersal predation with pehuén masting cycles.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, plant crop size seems to be a better predictor of seed losses than seed mass and it is possible that among year fluctuations in crop sizes may benefit plants from Cerrado. Populations of specialized seed predators may decline in years with no or low seed production, being more easily satiated in a subsequent year of high seed production as predicted by the predator satiation hypothesis in mast seeding species (Kelly & Sork 2002;Kon et al 2005). Future studies may evaluate this possibility.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately there is no data available to evaluate this hypothesis at the moment. Seed predation may also be subjected to temporal fluctuations that influence the satiation of predators (Kelly & Sork 2002;Kon et al 2005;Żywiec et al 2013;Bogdziewicz et al 2017). For instance, in tropical dry forests of Mexico, Erythroxylym havanense shows density-dependent seed predation in some years, while in other years seed predation fluctuate at random (Boege & Domínguez 2008).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations